On rural teachers in the districts of Strandasýsla and Húnavatnssýsla 1887–1905 - Guðmundsson, Bragi (Netla, 2021)
From shortly before the middle of the 18th century, Icelandic homes were obliged to provide children with instruction in religion and reading. This obligation was extended in 1880, when writing and arithmetic were added. The homes were supposed to provide the instruction, monitored by parish priests. By the middle of the 19th century, the need for schools for children and teenagers was generally recognized and they were founded one by one, primarily in urban areas. In the countryside, teaching mainly took place in homes and clergymen were supposed to monitor the children’s progress. Formal compulsory education was not introduced by law until 1907, with parents previously having been free to choose whether or not they sent their children to school.Many were concerned about the lack of schools but proponents of improved education often had to tackle obstacles deeply rooted in Icelandic history and culture, as well as in the firm belief that homeschooling was a cornerstone of society. There were also economic hindrances due to the high level of poverty amongst the general population and an ingrained reluctance to use public funds to cover communal expenses. Nevertheless, organised homeschooling was widely established in rural areas in the course of the 19th century, even though it was not available to all children and teenagers.This is the first of two planned articles based on data regarding rural teachers in two districts in the Húnaflói Bay area; that is, Strandasýsla and Húnavatnssýsla, prior to the formal introduction of compulsory education. The National Archives of Iceland preserve reports from 1887 and onwards that deal with grant applications from rural teachers. These reports provide valuable information that can be used for various observations. This article aims to shed some light on the individuals who were responsible for teaching between 1887 and 1905 and will from now on be referred to as teachers, whether or not they were formally certified as such. An attempt is made to reveal the people behind ...